HidroEsta, software for hydrological calculations - Villón-Béjar, Máximo (Revista Tecnología en Marcha, 2016)
This investigation, “HidroEsta, software for Hydrological Calculations” is oriented towards the creation of a computing tool using Visual Basic intended to facilitate and simplify difficult calculations that must be carried out in hydrological studies. The software allows making calculations of statistical parameters, as well as linear and non-linear, simple and multiple regression calculations, and polynomial regressions. It is also useful for evaluating if a series of data can be fitted to a series of distributions, and calculating design events with a given probability of occurrence, based on a seasonal variation curve or a duration curve; analyzing a storm and calculating maximum intensities based on pluviograms data; calculating flow measurements taken with windmills or current meters; calculating maximum flows with empirical and statistical methods; calculating evapotranspiration and hydric balance. Several numeric methods were used to solve the equations, selecting the most appropriate one for each case. The results of this work provide civil, agricultural engineers, and agronomists, hydrologists and other specialists who work in this field with a tool that enableZs them to carry out calculations, rapid simulations, and determine flow or precipitation for designs.